Land Cover and Soil Properties Influence on Forage Quantity in a Semiarid Region in East Africa - Anthony Egeru; Oliver Wasonga; Geofrey Gabiri; Laban MacOpiyo; John Mburu; Jackson Gilbert Mwanjalolo Majaliwa (Applied and Environmental Soil Science)
Soil properties contribute to the widely recognised resilience of semiarid areas. However, limited attention has been given in providing a scientific basis of how semiarid soil properties in the various land covers occur and how they influence forage quantity. This study investigated the influence of different soil properties and land cover types on herbaceous biomass quantity in the Karamoja subregion of Uganda. A completely randomized design in three land cover types (thickets and shrublands, woodlands, and savannah grasslands) was implemented. In each vegetation type, 50 × 40 m plots were demarcated with nested plots to facilitate clipping of the herbaceous layer. Composite soil samples at two depths (0–15 cm, 15–30 cm) were obtained from each plot. The results showed that soil properties varied across land cover types. Soil pH ranged between 6.9 and 8.1 and SOM, N, P, and K were generally low in all land cover types. Soil hydraulic properties revealed the existence of rapid to very rapid permeability in thickets/shrublands, grasslands, and woodlands. Percent change in soil properties (0–15 cm to 15–30 cm) was highest in P, Ca, Mg, Na, and SOM. In the grasslands, P positively (p≤0.01) influenced herbaceous biomass, whereas pH, K, Na, % sand, and % clay, N, and SOM had a negative relationship with herbaceous biomass (p≤0.05). Herbaceous biomass in the thickets/shrublands was negatively influenced by P, Ca, and Mg and % clay and positively by N and % silt (p≤0.05). Only N and SOM were significant determinants of herbaceous biomass in the woodlands (p≤0.05). The low level of soil nutrients observed in this study reveals the fragility of semiarid soils, indicating the need for sustainable landscape management.